English Foreign Language Teachers’ Attitude Towards and Practice of Using L1 in the EFL Classroom in Case of Goh and Gelila Highschool in South Omo Zone, Ethiopia - Gebreiyesus Mekt (International Journal of Integrative Sciences, 2023)
This study explores EFL teacher’s attitude forward and practice of using L1 in their classroom. It also considers that the context of using Aaraph in EFL classroom in high school level of  two selected schools in south Omo zone, South and North Ari woreda’s (Goh and Gelila High School). It was a descriptive study. The study employed mixed research method using questionnaire, interview, and observation. Data through questionnaires were collected from 11 EFL teachers and 263students from both school in south and north Ari. In addition, semi- structured interviews were carried out with five English teachers to get an in-depth understanding of their attitude forwards using Aaraph in EFL classrooms. Comprehensive sampling was employed so as to select and include all EFL teachers of the sampled secondary schools. Moreover, simple random sampling was used for selecting samples from the students for cross checking purpose. The study revealed that, almost all EFL teachers dominantly used Aaraph than target language. The purpose of EFL use of L1 while teaching English language was to translate concepts, to favour L1 use, and to support learners. EFL teachers don’t believe L1 has a negative effect on learner’s language learning. However, EFL Teachers have a negative attitude towards the use of L1 in the EFL classroom and implemented in different context of making a communication. The conclusion is that teachers employ L1 not only as a communication tool, but also as a supportive tool that helps in developing TL skills for students